Hypokalemia associated with mifepristone use in the treatment of Cushing’s syndrome - Sai Katta; Amos Lal; Jhansi Lakshmi Maradana; Pruthvi Raj Velamala; Nitin Trivedi (Endocrinology, Diabetes & Metabolism Case Reports, 2019)
Mifepristone is a promising option for the management of hypercortisolism associated with hyperglycemia. However, its use may result in serious electrolyte imbalances, especially during dose escalation. In our patient with adrenocorticotropic hormone-independent macro-nodular adrenal hyperplasia, unilateral adrenalectomy resulted in biochemical and clinical improvement, but subclinical hypercortisolism persisted following adrenalectomy. She was started on mifepristone. Unfortunately, she missed her follow-up appointments following dosage escalation and required hospitalization at an intensive care level for severe refractory hypokalemia.